Expression of connexin43 stimulates endothelial angiogenesis independently of gap junctional communication in vitro - Köpple, Christoph; Zhou, Zizi; Huber, Lena; Schulte, Matthias; Schmidt, Kjestine; Gloe, Torsten; Kneser, Ulrich; Schmidt, Volker-Jürgen; Wit, Cor de (International journal of molecular sciences, 2021)
Connexins (Cx) form gap junctions (GJ) and allow for intercellular communication. However, these proteins also modulate gene expression, growth, and cell migration. The downregulation of Cx43 impairs endothelial cell migration and angiogenetic potential. Conversely, endothelial Cx43 expression is upregulated in an in vivo angiogenesis model relying on hemodynamic forces. We studied the effects of Cx43 expression on tube formation and proliferation in HUVECs and examined its dependency on GJ communication. Expectedly, intercellular communication assessed by dye transfer was linked to Cx43 expression levels in HUVECs and was sensitive to a GJ blockade by the Cx43 mimetic peptide Gap27. The proliferation of HUVECs was not affected by Cx43 overexpression using Cx43 cDNA transfection, siRNA-mediated knockdown of Cx43, or the inhibition of GJ compared to the controls (transfection of an empty vector, scrambled siRNA, and the solvent). In contrast, endothelial tube and sprout formation in HUVECs was minimized after Cx43 knockdown and significantly enhanced after Cx43 overexpression. This was not affected by a GJ blockade (Gap27). We conclude that Cx43 expression positively modulates the angiogenic potential of endothelial cells independent of GJ communication. Since proliferation remained unaffected, we suggest that Cx43 protein may modulate endothelial cell migration, thereby supporting angiogenesis. The modulation of Cx43 expression may represent an exploitable principle for angiogenesis induction in clinical therapy.